Analysis of Challenges and Potential of the Village Economy Towards Competitive Village Development - Bayu Karunia Putra; Salahudin Salahudin (Publik : (Jurnal Ilmu Administrasi), 2022)
This article aims to analyze the challenges and potential of the village economy towards competitive village development. This topic is important and interesting, because with a well-managed village economy, related to it will create maximum village development later, because the village economy is the main foundation in relation to village development. The research method used is a qualitative method of data analysis, where the source and data are obtained through the results of data coding using Nvivo 12 Plus software. In this method, the researcher uses a qualitative approach to data analysis, where this method utilizes qualitative data and is described according to the analysis obtained. The data collection technique uses data analysis techniques through Nvivo 12 Plus software which is carried out by researchers to collect valid, complete, and relevant data related to the topic of the problem that is the object of research. The data analysis technique used analysis techniques based on data from Nvivo 12 Plus, where this technique was carried out by researchers to obtain the required data. The author finds that the government and the community must take part in making a positive impact on the progress of the village, because the challenges in developing the village are still often found whether it is from the bureaucracy that is still convoluted, the level of community participation is still minimal, funding is lacking, and so on. and so on, then the participation of the government and the community will certainly find efforts to overcome each of these problems.